PENGARUH STRES KERJA TERHADAP KINERJA PEGAWAI (Study Kasus KPU Provinsi Sulawesi Selatan) - Ridwan Ridwan (AkMen JURNAL ILMIAH, 2013)
This study aims to determine the effect of simultaneous work stress (job conflict, workload, working time, karaktcristik tasks, support group leadership and influence) on employee performance, 2) determine whether the stress of work (work conflict, workload, working time, the characteristics of tasks, support groups and the influence of leadership) simultaneously positive effect on employee performance, 3) determine whether the stress of work (work conflict, workload, work time, task characteristics, group support and influence leadership) partially significant effect on employee performance. The results of this study indicate that Taken together or simultaneously, six factors or variables that job stress is a factor into the analysis of the research work conflict, workload, work time, task characteristics, support groups, and the influence of leadership , meaningful and significant influence on the performance of employees in South Sulawesi Provincial Election Commission Office. Individually or farsial, six factors or variables that job stress is a factor into the analysis of the research work conflict, workload, work time, task characteristics, support groups, and the influence of leadership, meaningful and significant influence on the performance of employees in the Office of the Provincial Election Commission South Sulawesi.